5-(6-4x)-3=11

Simple and best practice solution for 5-(6-4x)-3=11 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5-(6-4x)-3=11 equation:



5-(6-4x)-3=11
We move all terms to the left:
5-(6-4x)-3-(11)=0
We add all the numbers together, and all the variables
-(-4x+6)+5-3-11=0
We add all the numbers together, and all the variables
-(-4x+6)-9=0
We get rid of parentheses
4x-6-9=0
We add all the numbers together, and all the variables
4x-15=0
We move all terms containing x to the left, all other terms to the right
4x=15
x=15/4
x=3+3/4

See similar equations:

| 0=-(3/4)y-2 | | -5(p+3/5)=-4 | | 1-8k=1-8k | | 18-5z+6z=9 | | -3x+10-x+6x=-20 | | -65=(3g-5)5 | | -b+4b=3b | | 6(2y+6)=4(9+3y | | 2x-1=4-1/2X | | 1/2x+1/2x=6 | | 3(y–4)+6/6–2=7 | | 2x-1=4-1/2 | | 15=26y | | X2+3x=270 | | |2x-2|=7 | | x/6-5=-14 | | 7+8r-4r=5r+5 | | 4-7m=1-4m | | 113=5x+53 | | x-5.1=3(x-5.5) | | 11=12−q | | x/3+3/5=5/12 | | x-5.1-3x-16.5=0 | | 14=-2(4r+5) | | 40x-10/13=15 | | -3-4(-5x+1)=93 | | 140+.7x=60+.9x | | -3x+10-x×6x=-20 | | 14=-2(4r+5 | | 3/x+1-1/2=1/3x+3 | | 5/12=n/21 | | (16-2x^2)/(16-x^2)^(1/2)=0 |

Equations solver categories